2020
DOI: 10.3390/diagnostics10040225
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ground Glass Opacities Can Be Useful to Describe Disease Activity in Systemic Sclerosis

Abstract: Interstitial lung disease (ILD) is the main cause of death in systemic sclerosis (SSc) patients. Usually, patients have lung involvement characterized by ground glass opacities (GGOs), but honeycombing (HC) is also possible. The Wells score is a semi-quantitative index, which is able to assess ILD by distinguishing its main components. The aim of this work is to evaluate the Wells score in relation to the disease activity (DA) index. We enrolled 40 consecutive SSc-ILD patients (26 diffuse cutaneous form, dcSSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…When a chest HRCT scan is performed on a subject who has a chest X-ray in the form of active TB, there is no visible On the chest HRCT scan, the most common type of lung lesion in SSc patients with pulmonary abnormalities was the type of GGO lesion, which were 46 subjects (82%). This is consistent with the study conducted by Sambataro et al 21 in 2020, which states that the type of GGO lesions often appears on the chest HRCT scan of SSc patients with pulmonary abnormalities.…”
Section: Discussionsupporting
confidence: 93%
“…When a chest HRCT scan is performed on a subject who has a chest X-ray in the form of active TB, there is no visible On the chest HRCT scan, the most common type of lung lesion in SSc patients with pulmonary abnormalities was the type of GGO lesion, which were 46 subjects (82%). This is consistent with the study conducted by Sambataro et al 21 in 2020, which states that the type of GGO lesions often appears on the chest HRCT scan of SSc patients with pulmonary abnormalities.…”
Section: Discussionsupporting
confidence: 93%
“…The data observed by HRCT clearly provides direct evidence of lung involvement. In a previous study, a correlation was observed between ground glass opacities measured by semiquantitative methods and DA in the diffuse cutaneous variant of SSc, but the method is bound to variability among observers (11). The correlation between QCT indexes and DA supports the possibility to overcome this limitation.…”
Section: Discussionmentioning
confidence: 74%
“…Several attempts have recently been made to standardise CT evaluation. Semi-quantitative scores have a good correlation with DA (11). These scores are burdened by relevant variability, even among expert observers (12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, none of these factors have been proven to influence significantly NVC [23][24][25]. Conflicting results are also reported regarding the association between PFTs and NVC in SSc, no association was reported in IPF and evidences in other ILDs are totally lacking [26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%